Rancang Bangun Aplikasi Konsultasi Makanan Sehat Bagi Penderita Diabetes Berbasis Mobile Menggunakan Teknologi J2ME - Rusdianto, Dedy Bagus; Lusiani, Titik; Sutanto, Teguh (Jurnal JSIKA, 2012)
The number ofdiabeticswhodoeatingarrangementsin accordance withhis conditionis muchlesscompared with notdoing it.Onereasonis the absence ofanindependentmediaconsultancythathelpspeople withdiabetesto consultfood.One solutiontoovercomethe above problemsis tomakeanapplicationconsultationshealthy foodfor diabeticsbasedmobileusingJ2MEtechnology. These applicationsrunonmobiledevicesare currentlyusersinIndonesia has increased.The applicationisexpected to beusedby diabeticsin regulatingeatingwellandin accordancewith theneedsofthe user´s body. Thusdiabetescanbe inhibitedtheir developmentsuffered.This systemcanprovideinformation onhealthyfoodsfor diabeticsandcansee thedevelopment ofconsultationthrough thegraphwiththe inputheight, weight, age, gender, type ofactivity, pregnancystatus, andtype offood.” Keywords :Mobile application, Diabetes, J2ME.